Some considerations on the semi-modal auxiliary verbs - CIUMACENCO, Valentina (Journal of Social Sciences, 2019)
This paper deals with the livelised cost of electricity from gaseous biofuels, such as biogas and bio-syngas, produced from biodegradable waste, using different technologies (internal combustion engines, gas turbine, fuel cells) at different capacities in the conditions of the Republic of Moldova, in case of non-use and use of thermal energy. The levelized cost of electricity was compared with the levelized energy supply tariff. Thus, it was demonstrated the feasibility of electricity production from biogas using internal combustion engines at any installed power, gas turbines with installed power starting from hundreds of kW and high power fuel cells, and the use of the bio-syngas for energy production is attractive in internal combustion engines and gas turbines with power greater than 1 MW. The technology of internal combustion engines proves to be more attractive, compared to gas turbine and fuel cells installations.